Adequate responses to plant protection policy - Jordán, László (Acta Agraria Debreceniensis, 2011)
The head of crop protection in the Central Agricultural Office offers a survey of the lately reconstructured official structure, outlines the sections of Central Directorate, sketches the roles of County Government Bureaues. To keep the standard of knowledge changes are necessary to make in the higher education of plant protection specialists. The prersentation will concern the contacts between researches made on universities and agricultural official directorates. It is analized the regulation of present and future pesticide usage, the possible alternatives of reduced quantity pesticide usage including the application of Integrated Plant Management (IPM) as well. The tasks of national activity according to the EU direcives about sustainable pesticide usage touch the problems of plant protection machinery and environment safety. It is summarized the tasks of official directorate, chamber of crop protection specialists, moreover practice of plant protection for the nearest future.